Alcohol Storylines in Television Episodes: The Preventive Effect of Countering Epilogues. Issue 8 (3rd August 2017) - Russell, Cristel Antonia; Russell, Dale Wesley; Grube, Joel W.; McQuarrie, Edward
Abstract : This experimental study assessed whether alcohol television storylines impact youth drinking attitudes and intentions and whether corrective epilogues can potentially moderate this impact. Television episodes were professionally produced to depict heavy drinking leading to either positive or negative consequences. The pro- and anti-alcohol episodes were shown alone or with an epilogue where a main character discussed the deleterious effects of excessive drinking. Attitudes toward drinkers and drinking intentions were measured subsequently, along with reactions to the episode and demographic data, among participants aged 14–17 using an online study. Exposure to the pro-alcohol episode was related to more positive attitudes toward drinkers. Including an epilogue after a pro-alcohol episode was related to more negative viewers' attitudes toward drinkers and lower drinking intentions compared to a pro-alcohol episode with no epilogue. By contrast, including an epilogue after an anti-alcohol episode was unrelated to attitudes toward drinkers or drinking intentions. Viewing a single television episode with a pro-alcohol message may lead to more positive attitudes toward drinkers. The finding that a brief epilogue may reduce the impact of the pro-alcohol storyline suggests easily implemented preventive strategies to counter the adverse impact of substance use portrayals in entertainment programming.